Поход Маркузе против марксизма - Баталов Эдуард Яковлевич (Против буржуазной идеологии, 1970)
Экземпляры: КХ (20120731) / Инвентарный номер: 501067 / Сис.шифр: 1Ф / Авт.знак: Б 28 / ГРНТИ: 02 / ББК: 87